Event-Related Potentials Related to Anxiety in Emotion-Attention Interaction. (7th October 2014) - Seo, Ssanghee; Kim, Bonghyun
Abstract : To identify neurological characteristics in accordance with anxiety under the interaction between emotion and attention, this study examines major ERP components when participants identify a target number by inhibiting task-irrelevant emotional face distractors. Experiments were conducted once per day at the same time for two days with 19 healthy adult men and women as required to study emotion-attention interaction. In this study, a variety of ERP components such as P100, N200, and P300 during experiment are significant. The amplitude and latency of the N200 component reflect both state and trait anxiety at all positions. This characteristic specially is prominently featured at Cz. Also, the latency of the late P300 component reflects the trait anxiety rather than state anxiety. The result of this study can help our understanding of the neurological responses related to anxiety during attentional control.